Multiple Angulated Mammography Reconstructions in Digital Breast Tomosynthesis for the Diagnosis of Microcalcifications – Added Value to Standard Stack Reconstructions and Synthesized Mammography - Neubauer, Jakob; Neubauer, Claudia; Wicklein, Julia; Mertelmeier, Thomas; Windfuhr-Blum, Marisa; Langer, Mathias (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose To compare ratings regarding the depiction, diagnostic accuracy and lesion characterization of conventional synthesized mammography (SM), multiple angulated mammography reconstructions (INSIGHT3D), and standard stack reconstructions in digital breast tomosynthesis for microcalcifications.Materials and Methods This is a retrospective, multicase, multireader study. We included patients with digital breast tomosynthesis (DBT), microcalcifications and histology over a period of four months in our institution and the same number of normal cases. Three radiologists, who were blinded to patient data, independently rated the depiction, distribution, morphology and BI-RADS score of microcalcifications in SM, INSIGHT3D and standard stack reconstructions. Deidentified images were presented in random order. Reading time was measured. Friedman and post hoc Nemenyi tests, Cochrane’s Q and post hoc Wilcoxon signed rank tests, Fleiss’ kappa and receiver operating characteristics were used for statistical analysis.Results We included 41 histopathologically proven and 41 normal cases. Depiction of microcalcifications was rated better in INSIGHT3D than in SM and better in stack reconstructions than in INSIGHT3D and SM (P < 0.001). The reading time was lower in SM and INSIGHT3D compared to stack reconstructions (P < 0.001). The diagnostic accuracy and inter-rater correlation were comparable between all tested modes of reconstruction.Conclusions INSIGHT3D has higher ratings regarding the depiction of microcalcifications compared to SM while maintaining a short reading time. Our preliminary assessment suggests that INSIGHT3D provides added value to SM.Key points Citation Format
Keywords: synthezised mammography; insight3D; image manipulation/reconstruction; breast; microcalcifications; digital breast tomosynthesis